CASE BASED LEARNING IN LANGUAGE TEACHING - Ayu Paramita Dharmayanti Putu (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2021)
Case-based learning (CBL) is an approach to promote students higher levels of cognition by applying their knowledge to real-world scenarios or environment in order to form new meanings of disciplinary problem and provide solution under the guidence of the instructor. Although case-based learning is initially designed for non-linguistic disciplines, lately it can be implemented in language teaching, in particular English for Specific Purposes (ESP). This article is purposed to discuss about the implementation of case based learning in language teaching. Case based learning carries multiple benefits for students in language teaching, such as providing opportunities to read, speak, listen, and write; introducing and practicing vocabulary and grammatical structures in the context of the case; and increasing learners’ participation, motivation and attitudes toward language study. With all benefits from case-based learning in language teaching, it also can be applied for all levels of students. However, there are some aspects that must be considered in applying case-based language teaching in English as foreign language in all level of students, they are the characteristic and type of case, procedure in implementing case based learning, and assessment in case based learning.